2018
DOI: 10.1136/bmjopen-2018-021889
|View full text |Cite
|
Sign up to set email alerts
|

Real-world persistence and adherence to oral antimuscarinics and mirabegron in patients with overactive bladder (OAB): a systematic literature review

Abstract: PurposeTo evaluate persistence and adherence of oral pharmacotherapy used in the treatment of overactive bladder (OAB) in a real-world setting.Materials and methodsSystematic literature searches of six electronic publication databases were performed to identify observational studies of patients with OAB treated with antimuscarinics and/or mirabegron. Studies obtaining persistence and adherence data from sources other than electronic prescription claims were excluded. Reference lists of identified studies and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
108
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 58 publications
(82 reference statements)
3
108
0
4
Order By: Relevance
“…Also in this group of patients, polypharmacy and the cognitive impairment seen with total anticholinergic load are relevant considerations . Retrospective data also show that persistence with mirabegron is higher than that observed with antimuscarinic agents …”
Section: Discussionmentioning
confidence: 88%
“…Also in this group of patients, polypharmacy and the cognitive impairment seen with total anticholinergic load are relevant considerations . Retrospective data also show that persistence with mirabegron is higher than that observed with antimuscarinic agents …”
Section: Discussionmentioning
confidence: 88%
“…For decades, anticholinergics such as tolterodine, solifencin, fesoterodine, and so on have been the chief pharmacotherapy for OAB. However, it is clinically observed that their usefulness is limited by modest efficacy and lack of bladder specificity, leading to well‐documented side effects including constipation, dry mouth, and dizziness 15,16 . Vibegron (RVT‐901; KRP‐114V) is a new selective β3‐adrenergic receptor agonist, which developed for treating OAB patients 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, in order to detect a change in BP monitoring intensity during treatment, regular check-ups are required, but the duration of treatment is often limited. More than 50% of patients have been reported to have stopped treatment after 1 month 29 or after the first prescription 30 (i.e. non-persistence), and after 1 year the supplied amount of mirabegron has been reported to cover <60% of the period.…”
Section: Discussionmentioning
confidence: 99%
“…non-persistence), and after 1 year the supplied amount of mirabegron has been reported to cover <60% of the period. 29 Alleviation of symptoms is a factor in nonpersistence with treatment for overactive bladder, and intermittent treatment is often observed. 29,30 Therefore, we allowed mirabegron treatment to contain gaps of up to 12 months, with the aim of ensuring that duration of treatment was long enough to allow comparison of quarterly BP monitoring rates before and after DHPC dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation